Determinants of Starbucks Purchasing Decision on Gen Z in Medan - Fangellica Victoria; Purnama Yanti Purba; Catherine, Catherine; Elfina Okto Posmaida Damanik (Cita konsultindo, 2025)
Starbucks is recognized for its unique flavor and premium-quality products, making it a favored destination for customers, particularly young individuals, to socialize and spend time at Starbucks outlets in Medan. In addition to product quality, factors such as engaging promotions and a comfortable store ambiance also play a role in influencing customers' purchasing decision. This study aims to evaluate and analyze purchasing decision for Starbucks beverages by examining the impact of product quality, social media, and store atmosphere. A descriptive quantitative approach was utilized, with accidental sampling applied to collect data from 100 respondents. Multiple linear regression was used for data analysis. The results indicate that product quality and social media have a positive and significant impact on purchasing decision. Conversely, the store atmosphere does not have a significant or positive effect when considered individually. However, when combined, product quality, social media, and store atmosphere significantly influence purchasing decision, explaining 51.7% of the variance, while the remaining 48.3% is attributed to other factors not covered in this study.